The role of natural resources in economic growth: New evidence from Pakistan - Aiza Shabbir; Shazia Kousar; Farzana Kousar (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - The purpose of this study is to investigate the role of natural resources in economic growth by taking evidence from Pakistan. Design/methodology/approach - Total five variables are used in this study, i.e. GDP, population density, water renewable resources, deforestation and the emissions of CO2, based on time series data from 1972 to 2016. The annual data is collected from World Development Indicators, Food and Agriculture Organization and Pakistan Economic Survey. Vector error correction model technique is applied to find out the long-run results. Findings - Results depict that all variables have a negative and significant relationship over the long run at 5% level of significance. It is observed that 1% increase in population accordingly will degrade GDP by 0.334496%. Correspondingly, 1% increase of water renewable resources will degrade GDP by 0.450647%. Findings are aligning with the study of. Moreover, 1% increase in deforestation will diminish GDP by 0.127821%. If we increase 1% of CO2, GDP will be reduced by 0.802420%. Research limitations/implications - Results depict that all variables have a negative and significant relationship over the long run at 5% level of significance. It is observed that 1% increase in population accordingly will degrade GDP by 0.334496%. Correspondingly, 1% increase of water renewable resources will degrade GDP by 0.450647%. Findings are aligning with the study of. Moreover, 1% increase in deforestation will diminish GDP by 0.127821%. If we increase 1% of CO2, GDP will be reduced by 0.802420%. Practical implications - Family planning may be our last hope. Viable and fruitful family planning ought to be introduced. Status of ladies should be brought up in the society by providing education and employment opportunities. Time of marriage ought to be brought up to 25 years in case of males and 23 in case of females; this can help in decreasing the number of births. Having a large population will not automatically translate into economic prosperity. Investment in well-being, education, sound economic policies and good governance will bring about accelerated economic growth. Originality/value - In recent years, the issue of worldwide water shortage has attracted increasing consideration within scholarly community, non-administrative organizations and the media. Water shortage is a significant and ever-increasing danger to the environment, human well-being, advancement, energy security and the worldwide food supply. This work will introduce real issues and requirements relating to water, environmental changes and their impact on economic growth of Pakistan.
Keywords: 330; CO2 emissions; Economic growth; Environmental Kuznets; Natural resources; Population growth; Water shortage